Brendan M. Walsh (1940-2016): The Economist at Work - Neary, J. Peter; Ó Gráda, Cormac (The Economic and Social Review, 2017)
Physically as well as intellectually, Brendan Walsh (BMW) bestrode the narrow world of Irish economics like a colossus for decades. In part this reflected his calm debating style, and his common-sense ability to synthesise a vast range of knowledge of the Irish economy. But it also reflected the fact that he published consistently and voluminously throughout his career.